Car Parking Practices And Challenges In Adama Town: The Case Of Bedhatu Kebele - Hawetu, Workineh (ASTU, 2021)
This Paper Examines The Car Parking Practices And Challenges In Urban Cities Of Adama With A View To Provide Effective Suggestions To Overcome The Challenges. Due To High Population Growth Increasing The Number Of Vehicles And Other Related Factors, The City Cannot Able To Meet The Ever-Increasing Demand For Car Parking Place .The Purpose Of This Study Is To Assess The Car Parking Practices And Challenges In Adama Town: The Case Of Kebele 07. The Study Was Aimed Showing The Trend, The Scarcity Of Car Parking Place, Haw Far The Supply Of The Car Parking Spaces Matched With The Demands Of The Car Parking Spaces, How Far The City Drivers Were Satisfied With The Car Parking Facilities And Finally To Recommend Better Ways Car Parking Management Systems. It Also Helps To Determine To What Extent Car Parking Had Effects On The City. The Results Of The Study Indicated That Un-Availability Of Car Parking Spaces Was A Major Problem For Traffic Flow And Development Of The City. Besides, It Was Also Learnt That Car Parking Has Major Social, Political And Economic Impact On The Growth Of The City. Finally, This Study Suggests That In Order To Reduce Traffic Congestions And Delays At Road Intersections Or Junctions In The City Such As On-Street Parking Should Be Discouraged And Adequate Off-Street Parking Facilities Should Be Provided.
Keywords: Parking, Challenges, Practice, Adama